Technology‐enabled collaborative care for youth with early psychosis: A protocol for a feasibility study to improve physical health behaviours. Issue 4 (3rd August 2020) - Selby, Peter; Vojtila, Lenka; Ashfaq, Iqra; Dragonetti, Rosa; Melamed, Osnat C.; Carriere, Rebecca; LaChance, Laura; Kohut, Sara Ahola; Hahn, Margaret; Mulsant, Benoit H.
Abstract: Aim: Individuals with psychotic disorders have poorer health outcomes and die earlier due to cardiovascular diseases when compared to healthy populations. Contributing factors include low levels of physical activity, poor nutrition and tobacco smoking. Currently, patients navigate a fragmented health‐care system to seek physical and mental health services, often without access to evidence‐based health promotion interventions, especially in non‐academic settings or rural areas, increasing client barriers at the individual and provider level. To address these gaps, we wish to test the feasibility and impact of a Technology‐Enabled Collaborative Care for Youth (TECC‐Y) model to improve healthy behaviours among youth with early psychosis. The model addresses geographical barriers and maldistribution of physical and mental health care. Methods: A randomized controlled trial, including youth (ages of 16‐29) with early psychosis (diagnosed in the past 5 years) residing in Ontario, Canada. Our primary outcome is client engagement. Secondary outcomes include smoking status, physical health and nutrition. Participants are randomly assigned to either a health coach supervised by a virtual care team, or a self‐directed learning group (e‐platform with psychoeducational materials). Assessments are conducted at baseline, 6, 12 and 24 weeks. Results: This paper presents the protocol of the study. Recruitment commenced in August 2018. This study was registered on 16 July 2018 on clinicaltrials.gov (Registry ID: NCT03610087). Conclusions: TECC‐Y will determine if a technology‐based collaborative care model engages youth with early psychosis, and whether this will be associated with changes in smoking, physical health and nutrition.